(3hGbY GdJQHjI GdQjGVjI aj GdKGfhjGJ GdQSejI aj efGWb GdQja GddHfGfj (B((3GdTMGQ(B-(3YGdjg(B)s - (3eWQ, jGSQs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2015)
(3ZOJ eeGQSI GdfTGW GdHOfj GdQjGVj, feW MjGI aj GdeLJeYGJ GdeYGUQI, EMJdJ GdJQHjI GdHOfjI ecGfI CSGSjI aj efGgL GdJYdje GdYGe dOjfG(B. (3CeG aj dHfGf, hHGdQZe ef UOhQ efGgL JYdjejI MOjKI CYWJ GdJQHjI GdQjGVjI ehbaG eejRkG aj LejY eQGMd GdJYdje GdYGe eG bHd GdLGeYj, aEf GdHGMK hef NdGd Yedg GdPj jJfGhd hGbY GdJQHjI GdQjGVjI aj GdQja GddHfGfj (B( (3efWbI GdTMGQ GdZQHj (B)(3, hLO Cf GdGgJeGe HGdJQHjI GdQjGVjI aj eQMdI GdJYdje GdKGfhj aj gPg GdefWbI djS HGdbOQ GdcGaj, aYeO aj gPG GdHMK Edi GdJYQa Ydi GdeTcdGJ GdeSHHI dgPG GdhGbY ef NdGd GdHMK GdhUaj, hCLQi GdHMK Ydi YjfI bhGegG (B100 (3WGdH hWGdHI aj KdGK KGfhjGJ YOO WdGHgG (B768 (3WGdHG(B. (3hCXgQJ fJGFM GdHMK Cf GdeTcdGJ GdCSGSjI GdJj JMhd Ohf eTGQcI GdWdGH HLOjI aj MUU GdJQHjI GdQjGVjI JJeKd HJOfj eSJhi GddjGbI GdHOfjI hGdeeGQSI GdQjGVjI(B. (3hbO ChUi GdHGMK HGdYed Ydi EcSGHge GdeYGQa GdCSGSjI Mhd GdJQHjI GdQjGVjI HgOa JbOjQ OGaYjJge(B. (3ceG ChUi HJaYjd OhQ hRGQI GdJQHjI hEOGQGJ GdeOGQS, hJfTjW Yed GdCfOjI GdQjGVjI hJhajQ GdeOQSjf hGdJLgjRGJ(B.s
(3GdfhY (B: (3QSGdIs
Keywords: (3YGdjgs; Al Shahar Aley; Al Shahar Aley; Education; Milieu Socio-Culturel; Public Sector Secondary Education Sport; Secteur Public Cycle Secondaire Education Sportive; Socio-Cultural Milieu; (3GdJYdje GdQSej GdeQMdI GdKGfhjI JYdje GdQjGVIs; (3GdTMGQs; (3GdhSW GdKbGaj GdGLJeGYjs